CoReflect: Web-Based Inquiry Learning Environments on Socio-scientific Issues - Redfors, Andreas; Hansson, Lena; Iolie Nicolaidou; Asher, Itay; Tabak, Iris; Papadouris, Nicos; Avraam, Christakis; Kyza, Eleni A. (My University, 2014)
This chapter describes the development of the web-based inquiry learning environments as part of CoReflect, a finalized 3-year EC project involving seven countries. In CoReflect, interactive web-based materials for data-driven inquiry using the web-based platform STOCHASMOS were developed. The learning environments (LEs) embrace the guided constructivist approach to learning and support collaborative and reflective work. Teachers were engaged in the design and implementation of the LEs so that a mechanism could be developed for subsequent scale-up within Europe. All LEs were implemented at least three times and in two different countries. The final versions are available from coreflect.org. This chapter focuses on experiences from the first two implementations and gives an overview of the implementations of four LEs, discussing findings and student outcomes. Results are related to earlier research on the use of socio-scientific issues in the teaching of science.
Keywords: CoReflect; Web-Based Inquiry Learning Environments; Socio-scientific Issues; Education